Metaphor Beyond Branding: From the Perspective of Cultural Semiotic - Mohd Fauzi Harun; Khairol Ezedy Abd Rahman; Ida Puteri Mahsan; Muliyati Mat Alim; Nik Narimah Nik Abdullah; Fareez Vincent Amos (Journal of International Business, Economics and Entrepreneurship)
Metaphors can help brands tell compelling stories about their products and values, but they also can create false associations between a product and unrelated concepts. Thus, the study explores the role of cultural values and beliefs in shaping the use of metaphors in Malaysian food product branding. A semiotic analysis is run on five food packaging designs to understand the symbolic meanings encoded to uncover the hidden meanings and associations that influence consumer perceptions and behaviors. Data analysis involves a systematic process of identifying, analyzing, and interpreting signs, and symbols to uncover their underlying meanings and significance. Findings showed that brand elements closely related to a specific cultural attribute can be a complicated topic because they can also be manipulative for branding or marketing purposes. The existence of metaphor in multiple brand elements enhances the brand's image and appeal by evoking positive emotions, aspirations, or associations. This study contributes to the conceptualization of the relationship between visual metaphor and brand relationship in the field of visual communication. Thus, it helps marketers create effective brand positioning that resonates with consumers' relevant cultural symbols and meanings and avoids costly marketing blunders.